2007
DOI: 10.2139/ssrn.1080533
|View full text |Cite
|
Sign up to set email alerts
|

What Explains the Spread between the Euro Overnight Rate and the ECB's Policy Rate?

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…If the ARCH test (Engle 1982) for standardized residuals revealed heteroscedasticity, we modeled the nonlinear dependencies via SV model (see the ''Appendix'' for details). Based upon the findings in the literature (Wuertz 2003;Linzert and Schmidt 2008;Schianchi and Verga 2006;Abbassi and Nautz 2010), as well as our previous findings (Kliber et al 2011;Kliber and Płuciennik 2011a) we decided to use the following explanatory variables:…”
Section: Analysis Of the Spread Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the ARCH test (Engle 1982) for standardized residuals revealed heteroscedasticity, we modeled the nonlinear dependencies via SV model (see the ''Appendix'' for details). Based upon the findings in the literature (Wuertz 2003;Linzert and Schmidt 2008;Schianchi and Verga 2006;Abbassi and Nautz 2010), as well as our previous findings (Kliber et al 2011;Kliber and Płuciennik 2011a) we decided to use the following explanatory variables:…”
Section: Analysis Of the Spread Dynamicsmentioning
confidence: 99%
“…In this sense the WIBOR rate is the transactional one (for more details see-ACI Polska webpage). 5 Linzert and Schmidt (2008), in order to explain the dynamics of EONIA spread, used a variable bid-tocover ratio which is defined as the ratio between the total bid volume of monetary bills and the amount covered. It is interpreted as a degree to which the liquidity surplus is absorbed by the central bank.…”
Section: Analysis Of the Spread Dynamicsmentioning
confidence: 99%
“…He points out the importance of the size of the open market operations for the uncertainty of the outcome of the liquidity auction and links it to the increase in the price of the bids. His theoretical results are corroborated, among others, by the empirical applications of Linzert and Schmidt [15]. Finally, the implications of the recent financial crisis on the Euro money markets are analyzed in Cassola and Morana [3], Eisenschmidt, Hirsch and Linzert [6] as well as Eisenschmidt and Tapking [5].…”
Section: Introductionmentioning
confidence: 81%
“…This central aim of monetary policy implementation has never been an easy task. Even before the financial crisis, a puzzling and unintended upward trend in the spread between the European overnight rate (Eonia) and the MRO rates indicated that the monetary transmission mechanism is not sufficiently understood, see Linzert and Schmidt (2011). 1 Since the start of the financial crisis, spreads between the Eurosystem's main refinancing rates and the money market rates have been huge and persistent.…”
Section: Non-technical Summarymentioning
confidence: 99%